Optimizing of Nanocellulose Extraction From Highland Bamboo Arundinaria Alpina for Sustainable Bio-Nanomaterials via Response Surface Methodology - Kafi Mohamed Hamed; Ermias Girma Aklilu; Temesgen Abeto Amibo; Ebise Getacho Bacha (Advances in Polymer Technology)
Nanocellulose (NC) extraction from agricultural waste and lignocellulosic biomass residues has drawn considerable interest due to its low cost and wide availability. The environmental issues linked to nonrenewable materials have underscored the need for renewable alternatives that are biocompatible, biodegradable, and eco-friendly. This study aimed to investigate the potential of Ethiopian highland bamboo Arundinaria alpina for NC extraction by using acid hydrolysis. An experimental design incorporating response surface methodology (RSM) was applied to identify the optimal hydrolysis process parameters for NC extraction. The optimum conditions for NC extraction were a reaction time of 60 min, temperature of 40°C, and acid concentration of 61.40 wt%, with a yield of 43.15%. Bamboo and extracted NC were characterized for their chemical composition, particle size distribution, and crystallinity, using Fourier-transform infrared spectroscopy (FTIR), dynamic light scattering (DLS), and X-ray diffraction (XRD), respectively. The resulting NC had a particle size of 79.64 nm. XRD analysis revealed the crystallinity indices of the bamboo and its corresponding NC was 44.60% and 74.07%, respectively. These results indicate that highland bamboo A. alpina is a promising lignocellulosic source for sustainable NC extraction, optimization, and industrial applications.